2018
DOI: 10.1093/nar/gky980
|View full text |Cite
|
Sign up to set email alerts
|

NucMap: a database of genome-wide nucleosome positioning map across species

Abstract: Dynamics of nucleosome positioning affects chromatin state, transcription and all other biological processes occurring on genomic DNA. While MNase-Seq has been used to depict nucleosome positioning map in eukaryote in the past years, nucleosome positioning data is increasing dramatically. To facilitate the usage of published data across studies, we developed a database named nucleosome positioning map (NucMap, http://bigd.big.ac.cn/nucmap). NucMap includes 798 experimental data from 477 samples across 15 speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 33 publications
(31 reference statements)
0
28
0
Order By: Relevance
“…MNase-seq data were from Mieczkowski et al 2016 sample GSM2083140 [ 50 ], and analyzed as previously described [ 51 , 52 ]. Additional analysis of MNase-seq datasets from [ 53 ] was performed using the NucMap database [ 54 ] using nucleosome positions determined with DANPOS or iNPS [ 55 , 56 ]. Symmetry of nucleosome occupancy at p63BS was determined with ArchAlign with 0-bp shifts and region reversal enabled [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…MNase-seq data were from Mieczkowski et al 2016 sample GSM2083140 [ 50 ], and analyzed as previously described [ 51 , 52 ]. Additional analysis of MNase-seq datasets from [ 53 ] was performed using the NucMap database [ 54 ] using nucleosome positions determined with DANPOS or iNPS [ 55 , 56 ]. Symmetry of nucleosome occupancy at p63BS was determined with ArchAlign with 0-bp shifts and region reversal enabled [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nucleosome occupancy models trained on yeast data have been reported to produce predictions that correlate well with nucleosome maps from other organisms (Awazu, 2017; Gupta et al, 2008). However, we found that applying the in vitro and in vivo ChromWave models to 23,156 human promoter regions produced terrible agreement with MNase-seq datasets (Gaffney et al, 2012; Zhao et al, 2018), with average Pearson correlation coefficients of 0.002 and −0.0003, respectively.…”
Section: Resultsmentioning
confidence: 90%
“…NucMap (http://bigd.big.ac. cn/nucmap) (Zhao et al, 2019), the first database of genomewide nucleosome positioning maps, contains 15 plant nucleosomes from different developmental stages and/or tissues. Taken together, all these resources are publicly available and free to use.…”
Section: Molecular Plantmentioning
confidence: 99%